Effect of afzelin on inflammation and lipogenesis in particulate matter-stimulated C. acnes-treated SZ95 sebocytes - Hong, Ji Yeon; Choi, Yong Hee; Roh, Yoon Jin; Lee, Mi-Kyung; Zouboulis, Christos C.; Park, Kui Young (Frontiers in Medicine, 2025)
BackgroundAfzelin, a flavonoid (kaempferol 3-O-α-L-rhamnopyranoside) isolated from Thesium chinense, is known for its potent anti-inflammatory properties. However, its effects on the molecular aspects of inflammation and lipogenesis in SZ95 sebocytes has not been investigated.ObjectiveThis study aimed to (i) investigate inflammatory and sebum secretion changes when a Cutibacterium acnes-treated immortalized human sebocyte cell line (SZ95) is exposed to particulate matter (PM) and (ii) examine the effects of afzelin on these.MethodsTo investigate the effect of afzelin on PM- and C. acnes-treated SZ95 sebocytes, we injected heat-killed C. acnes into SZ95 cells to induce acne-like status. Thereafter, the SZ95 sebocytes were treated with PM and subsequently with afzelin. The gene expression profile was determined using real-time polymerase chain reaction analysis, and protein expression was confirmed via western blotting and immunofluorescence. Intracellular lipid droplet formation was investigated using Nile Red O staining.ResultsPM treatment upregulated the mRNA and protein expression levels of inflammatory cytokine and lipogenic genes in C. acnes-treated SZ95 sebocytes. Furthermore, intracellular lipid-droplet accumulation increased when C. acnes-stimulated SZ95 cells were exposed to PM. Interestingly, the upregulated inflammatory and lipogenic gene expression induced by C. acnes and PM was attenuated by afzelin treatment.ConclusionsThis study's findings indicate that PM potentially aggravates acne by acting on both inflammation and sebum secretion. They also reveal afzelin's ability to suppress these phenomena by not only suppressing inflammatory cytokine expression but also inhibiting sebogenesis. These findings confirm afzelin's potential therapeutic role in improving PM-exacerbated acne.